Frequent and Flexible: Options for Reporting Guidelines for Biennial Update Reports - Ellis, Jane (OECD/IEA Climate Change Expert Group Papers, 2011)
The Cancun Agreements outlined the list of topics to be included in biennial reports and indicated that guidelines for them were to be developed, but provided limited guidance on their structure and content. This paper proposes a structure for biennial reports for both developed and developing countries under the UNFCCC, and outlines possible reporting formats by which countries could submit this information.